Evolution of the binder gel in carbonation-cured Portland cement in an acidic medium. (July 2018) - Seo, J.H.; Park, S.M.; Lee, H.K.
Abstract: The present study investigated the evolution of a binder gel in carbonation-cured Portland cement in an acidic medium. Three types of Portland cement with varying chemical compositions were carbonation-cured and exposed to H2 SO4 or HCl. An acid attack induced significant changes in the local environment of Al in normally cured cement showing the formation of ettringite and Friedel's salt, while the local environment of Al in carbonation-cured cement mainly consisted of a tetrahedral aluminate structure and showed much less structural alteration. A thermal analysis showed that the carbonation products of belite were more stable than those of alite, with less gypsum formation under H2 SO4 in the cement with relatively more belite. Depolymerization of the carbonation product, Ca-modified silicate gel, was observed in the samples immersed in acid.